1996 Olympic Games in Atlanta: The best male volleyball-teams: Yugoslavia - Fröhner, B.; Zimmermann, B. (The Coach, 1997)
With its bronze medal win in the 1995 European Championship Yugoslavia has already surprised the experts after its return to the international volleyball scene. Without international matches - even though the majority of the players plays abroad - the team convinced with a well developed play concept and well trained players. Thus the victory in the Olympic qualification tournament in Munich was logical. Already at this time the team recommended itself for a good result in the Olympic tournament. The team which was very compact and highly motivated is made up of experienced players as Brdovic, Petrovic and Tanaskovic and of younger technically well trained players (Mester, Batez and Vujevic) which very good substitutes in the team. Yugoslavia especially impressed with good performances in the initial actions of several play complexes (service and serve reception).